Injury and Injury Prevention in United States Para Swimming: A Mixed-Methods Approach - Jay Salerno; Stephanie Tow; Elizabeth Regan; Stephen Bendziewicz; Matthew McMillan; Shana Harrington (International Journal of Sports Physical Therapy)
# Background